PENEGAKAN HUKUM TERHADAP PELANGGARAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT DI MASA PANDEMI COVID-19 (STUDY KASUS DI CABANG KEJAKSAAN NEGERI DELI SERDANG DI PANCUR BATU) - Rinda Adida Sihotang; Triono Eddy (JURNAL DOKTRIN REVIEW, 2023)
The health protocol was formed with the aim that people can continue to carry out their activities safely and not endanger the security or health of others, by enforcing the law for violations of the Implementation of Restrictions on Community Activities (PPKMI). This study aims to analyze legal arrangements regarding the implementation of restrictions on community activities during the corona pandemic, to analyze law enforcement against violations of imposing restrictions on community activities during the corona pandemic and to analyze obstacles to law enforcement during the corona pandemic. This research method uses empirical research by conducting interviews at the Deli Serdang District Attorney's Office in Pancur Batu. Based on research resultsfrom 2020 to 2022 , Pancur Batu Cabjari handled 1 (one) PPKM violation committed by Hairos Waterpark, the handling mechanism was first Cabjari Deli Serdang in Pancur Batu received a file from the Medan Polrestabes regarding PPKM Prokes violations at Hairos Waterpark. After the file is declared complete, the file is transferred to the Lubuk Pakam District Court. The obstacles faced by the prosecutor at the Deli Serdang District Attorney's Office in Pancur Batu in enforcing the law during the corona pandemic were the difficulty in summoning expert witnesses, and the absence of public witnesses who were present at the activities that violated PPKM carried out by